Immediate and delayed complications of adenotonsillectomy - Sebastian, Gerald P.; Thiagarajan, Balasubramanian; Devadason, Pethuru (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Tonsillectomy with or without adenoidectomy is the commonest pediatric otorhinolaryngological procedure. The aim of the present study was to compare the intraoperative (immediate) and postoperative (delayed) complications between in conventional and coablation tonsillectomy in children. Methods: This observational study was conducted among 100 children between 5 and 15 years who had conventional tonsillectomy and 50 children who had coblation tonsillectomy. Intraoperative and postoperative complications were observed and compared between two groups. Results: Of the total 150 children, 64 (42.7%) were males and 86 (57.3%) were females with mean age of 9.42±2.67 years. Common preoperative symptoms were odynophagia (96.0%), throat pain (95.3%) and difficult swallowing (89.3%). Among the intraoperative anesthetic complications, compression of endotracheal tube was observed in 19 (12.7%), accidental extubation in 10 (6.7%) and dislodging of loose tooth in 9 (6.0%) patients. Regarding intraoperative surgical complications, primary hemorrhage was seen in 43 (28.7%), edema uvula in 39 (26.0%) and pillar injury in 33 (22.0%) patients. Commonest postoperative complication was oropharyngeal pain (18.7%) followed by primary hemorrhage (14.0%) and nausea, vomiting (13.3%). Immediate complications like primary haemorrhage (p value 0.0001) and uvula edema (p value 0.018) were significantly associated with conventional tonsillectomy group while delayed complications like secondary haemorrhage (p value 0.011) and referred otalgia (p value 0.0001) were with coblation tonsillectomy group. Conclusions: Compression of endotracheal tube and primary hemorrhage were the commonest intraoperative anesthetic and surgical complication respectively. Immediate complications were significantly associated with conventional tonsillectomy group while delayed complications were with coblation tonsillectomies.